Pahang state exco passes biodiversity biotechnology strategic action plan! - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Mohamad Najib, Mohammad Nor (Penerbit UMP, 2008)
SEPT 3, KUANTAN: Pahang will include a one stop biotechnology center in the main technology park in Gambang, boosting the growth of the Knowledge Corridor of University Malaysia Pahang (UMP, International Islamic University Malaysia (IIUM) and University Technology MARA (UiTM)in the area.